PREPARATION OF IMPLANT-PROSTHETIC DISINFECTANT SOLUTION BY CHITOSAN, GREEN SYNTHESIZED SILVER NANOPARTICLES USING Cymbopogon citratus, Azadirachta indica, Melaleuca alternifolia AND EVALUATION OF ITS ANTIMICROBIAL PROPERTIES-AN INVITRO STUDY (Journal of Pharmaceutical Negative Results, 2023)
AIM: The aim of the study is to synthesize an implant-prosthetic disinfectant solution by a mixture of green synthesized silver nanoparticles using Cymbopogan citratus, Azadirachta indica, Melaleuca alternifolia and chitosan and to perform characterization tests and evaluate its antimicrobial activity .MATERIALS AND METHODS: 1 gram of neem powder was mixed with 100ml of water and made to boil for 10 min and filtered. 2 grams of lemongrass powder was mixed with 100ml of water, boiled for 10 min and filtered. Both the filtered extracts were mixed together and 40ml of the obtained extract was stored separately. 0.018 g of silver nano particle powder was mixed with 60ml of distilled water and chitosan solution with 1 ml of tea tree oil and the 40ml of the stored extract was mixed to finally obtain 100ml of final substrate.The final substrate was allowed to undergo reduction procedure ,centrifuged then dried in hot air over at 80 degree celcius .The obtained powder was scraped and further characterized using UV-Visible spectrophotometer and Scanning Electron Microscope(SEM). The anti microbial activity was also analyzed by incubating the coated prosthetic component with prepared disinfectant solution(test) and ethanol (control) in strains of E.coli,S.Aureus,E.fecalis. and the results were statistically compared using independent-t Test.RESULTS: The UV-visible-spectroscopy results of the prepared solution showed peak around 400 nm-450 nm confirming the presence of silver nanoparticles. The scanning electron microscope tests revealed that the silver nanoparticles were seen between 37 nm- 43 nm and were biconcave ,triangular rod shaped .The length and the width corresponding to the zone of inhibition around healing abutment (HA) and the Impression coping (IC) were measured. Independent t-test revealed that the antimicrobial property of the prepared disinfectant solution was superior to that of the standard ethanol solution , signifying the extension of its use in the clinical practice.CONCLUSION: The present study revealed that the prosthetic disinfectant solution is effective in controlling the risk of peri- implant infection in chair side clinical use. The silver nanoparticles could be synthesized in a simple, eco-friendly method using Cymbopogon citratus ,Azadirachta indica, extract. Hence, it can be employed in large scale production for ensuring high patient oriented successful treatments and also can be used to prevent the cross-contamination among dentists and lab professionals.